Influence of readability on popularization of internet resources - Basyuk, Taras (Lviv Polytechnic National University, 2018)
The article analyzes the influence of readability of the content on the popularization of Internet resource. The analysis of known methods for content readability determination, as additional component of popularization has been carried out. In researching, an algorithm for determining the basic level of readability has been developed, and recommendations for its application have been provided in order to enter the TOP results query. The question of determining the parameters of graphic design of the content is considered and recommendations on their application in the process of designing the Internet resource are provided. The research conducted creates the preconditions for further study of the subject and formation of mathematical support for automatic content rewriting depending on the required level of readability.
Keywords: readability; Internet resource; popularization; relevance; search engines